Evaluasi Jaringan Drainse Perkotaan di Jalan Raya Kemang, Kabupaten Bogor - Sungkana, Bagas Krya; Heryansyah, Arien; Wicaksono, Muhammad Hasan; Syaja'ah, Siti Kholifah (Universitas Ibn Khaldun, 2026)
Inundation on Jalan Raya Kemang (the Parung-Bogor road section in the Kemang area) is a common problem, especially during the high-intensity rainy season, disrupting public mobility and causing traffic congestion. This study aims to identify the factors causing the inundation and to evaluate the existing conditions of the drainage network system in the area. The methods used include hydrological and hydraulic analysis. Hydrological analysis is utilized to calculate the design flood discharge, while hydraulic analysis is used to analyze the capacity of the existing drainage channels.The results of the hydrological analysis show that the total design flood discharge from upstream to downstream is 1.08 m³/s. The hydraulic analysis on the existing channel dimensions of (1.2 x 1) meters indicates a channel capacity of 1.51 m³/s. Theoretically, the channel dimensions are capable of accommodating the design discharge. However, field observations show that the main factor causing the inundation is the presence of mud and sand sedimentation, approximately 30 cm high, inside the channels. This sedimentation causes a significant reduction in flow capacity. After accounting for the sedimentation, the channel capacity decreases to 0.962 m³/s, which is smaller than the design discharge at the inundation point (0.977 m³/s), causing water to overflow onto the road. Furthermore, the lack of drainage inlets is also a contributing factor to the inundation.It is concluded that the inundation on Jalan Raya Kemang is not caused by inadequate channel dimensions but rather by high sedimentation and a lack of drainage inlets